Spherical silica particles and resin composition using the same

By adjusting the surface state and heating process of spherical silica particles, controlling their specific surface area and the number of detached water molecules, the problem of difficulty in reducing the dielectric loss tangent in the prior art is solved, a lower dielectric loss tangent is achieved, and the signal transmission efficiency of high-frequency band equipment is improved.

CN118103329BActive Publication Date: 2025-03-04DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280069475.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-20
Filing Date
2022-10-07
Publication Date
2025-03-04
Estimated Expiration
2042-10-07

AI Technical Summary

Technical Problem

When existing spherical silica particles are filled into the resin, the dielectric loss tangent is difficult to effectively reduce, affecting the signal transmission efficiency of high-frequency band equipment.

Method used

By controlling the surface state of the spherical silica particles and the number of water molecules separated during heating, the specific surface area is between 0.1 and 2.0 m2/g, and the number of water molecules separated is within the range of 0.001 and 0.010 mmoL/g, thereby reducing the dielectric loss tangent.

Benefits of technology

A lower dielectric loss tangent is achieved when filling in resin, and the signal transmission efficiency of high-frequency band devices is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118103329B_ABST
    Figure CN118103329B_ABST
Patent Text Reader

Abstract

The present invention provides spherical silica particles that can achieve a lower dielectric loss tangent when filled into a resin and a resin composition using the spherical silica particles. The present invention is a spherical silica particle (X), wherein when the spherical silica particle (X) is heated from 50°C to 1000°C at a heating rate of 25°C / min, the number of water molecules released from the spherical silica particle (X) is 0.001 to 0.010 mmoL / g; the specific surface area is 0.1 to 2.0 m 2 / g. The present invention provides a resin composition comprising the silica particles (X) and at least one resin selected from a thermoplastic resin and a thermosetting resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to spherical silica particles and a resin composition using the spherical silica particles. Background Art

[0002] In recent years, with the increase in the amount of information communication in the communication field, the effective use of high-frequency band signals in electronic equipment, communication equipment, etc. has become increasingly widespread. On the other hand, there is also a problem that the transmission loss of circuit signals increases due to the application of high-frequency band signals to the above-mentioned equipment. Therefore, materials used in devices for high-frequency bands are required to have a low dielectric loss tangent. Transmission loss is roughly composed of conductor loss due to the skin effect of wiring and dielectric loss due to the characteristics of the dielectric material of the insulator constituting electrical and electronic parts such as substrates. Dielectric loss is proportional to the first power of frequency, the half power of the dielectric constant of the insulator, and the first power of the dielectric loss tangent, so materials used in devices for high-frequency bands are required to have both low dielectric constants and dielectric loss tangents.

[0003] The dielectric properties of ceramic materials for GHz bands are recorded, for example, in non-patent literature 1, but they are all properties of sintered substrates. The dielectric constant of silicon dioxide is relatively small, and the quality coefficient index Qf (the value obtained by multiplying the inverse of the dielectric loss tangent by the measured frequency) is about 120,000, so it is expected to be a ceramic filler with low dielectric constant and low dielectric loss tangent. From the viewpoint of being easily blended into a resin, the closer its shape is to a sphere, the more preferred it is. Spherical silicon dioxide particles can be manufactured, for example, by a flame melting method (patent literature 1). Regarding spherical silicon dioxide particles synthesized by such a method, it is expected to be used in the equipment used in the above-mentioned high frequency band.

[0004] There are many polar functional groups such as adsorbed water and silanol groups on the surface of spherical silica particles, which easily deteriorates the dielectric loss tangent. Methods for reducing adsorbed water and silanol groups on the surface of spherical silica particles are described in, for example, Patent Documents 2 to 4, but the dielectric loss tangent reduction effect of the spherical silica particles obtained by these methods is insufficient.

[0005] Patent Document 1: International Publication No. 2016 / 031823

[0006] Patent Document 2: Japanese Patent No. 2926348

[0007] Patent Document 3: Japanese Patent Application Publication No. 2020-097498

[0008] Patent Document 4: Japanese Patent Application Publication No. 2020-138880

[0009] Non-patent literature 1: International Materials Reviews vol.60No.7Supplementary data (2015) Summary of the invention

[0010] Therefore, an object of the present invention is to provide spherical silica particles that can achieve a lower dielectric loss tangent when filled into a resin, and a resin composition using the spherical silica particles.

[0011] The present inventors focused on the surface state of spherical silica particles and the number of water molecules released from the particles when the spherical silica particles were heated and evaluated. As a result, they found that as long as the specific surface area of ​​the spherical silica particles is small and the number of water molecules released when heated from 50°C to 1000°C is within a certain range, a lower dielectric loss tangent can be achieved, thereby completing the present invention.

[0012] That is, the present invention has the following aspects.

[0013] [1] A spherical silica particle (X), wherein when the spherical silica particle (X) is heated from 50°C to 1000°C at a heating rate of 25°C / min, the number of water molecules released from the spherical silica particle (X) is 0.001 to 0.010 mmoL / g, and the specific surface area is 0.1 to 2.0 m 2 / g.

[0014] [2] The spherical silica particles (X) according to [1], wherein the average circularity of the spherical silica particles (X) is 0.85 or more.

[0015] [3] The spherical silica particles (X) according to [1] or [2], wherein the surface fractal dimension of the spherical silica particles (X) is 1.0 to 2.3.

[0016] [4] The spherical silica particles (X) according to any one of [1] to [3], wherein the average particle size of the spherical silica particles (X) is 1 to 30 μm.

[0017] [5] The spherical silica particles (X) according to any one of [1] to [4], wherein the spherical silica particles (X) are surface-treated with a surface treatment agent.

[0018] [6] The spherical silica particles (X) according to any one of [1] to [5], which are used for resin filling.

[0019] [7] A resin composition comprising the spherical silica particles (X) according to any one of [1] to [6], and at least one resin selected from a thermoplastic resin and a thermosetting resin.

[0020] According to the present invention, it is possible to provide spherical silica particles that can achieve a lower dielectric loss tangent when filled into a resin, and a resin composition using the spherical silica particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an electron microscope photograph showing one form of the spherical silica particles (X) of the present invention.

[0022] Figure 2 This is an electron microscope photograph of amorphous spherical silica particles before classification. DETAILED DESCRIPTION

[0023] Hereinafter, the present invention is described in detail, but the present invention is not limited to the following modes and can be appropriately changed and implemented within the scope that does not hinder the effect of the present invention. When a specific description described in one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments. In addition, the description of "to" in this specification means "above and below". For example, "0.001-0.010mmoL / g" means above 0.001mmoL / g and below 0.010mmoL / g. In addition, the "silicon dioxide particles" disclosed in the present invention refer to an aggregate of multiple particles.

[0024] [Spherical silica particles (X)]

[0025] The spherical silica particles (X) of the present invention are characterized in that when the spherical silica particles (X) are heated from 50°C to 1000°C at a heating rate of 25°C / min, the number of water molecules released from the spherical silica particles (X) is 0.001 to 0.010 mmoL / g, and the specific surface area is 0.1 to 2.0 m 2 / g. The spherical silica particles (X) of the present invention can achieve a lower dielectric loss tangent when filled into a resin. In addition, the "spherical silica particles" referred to in this specification refer to silica particles whose projection images (including stereoscopic images and top views) have a shape close to a circle when the silica particles are observed under a microscope or the like.

[0026] In the present invention, the number of water molecules released from the spherical silica particles (X) can be measured by the following method.

[0027] <Method for measuring the number of desorbed water molecules>

[0028] Using a gas chromatograph mass spectrometer (e.g., manufactured by JEOL Ltd., product name: JMS-Q1500GC) and a thermal decomposition device (e.g., manufactured by Frontier Lab, product name: PY-3030D), 15 μg of spherical silica particles are heated from 50°C to 1000°C at a heating rate of 25°C / min in a helium atmosphere. The area value of the mass spectrum (m / z=18) obtained in the range of 50°C to 1000°C is calculated, and the number of water molecules detached is calculated from the calibration curve. In addition, for the calibration curve, the area value of the number of water molecules detached (m / z=18) of an aluminum hydroxide sample (e.g., manufactured by Kojundo Chemical Research Institute Co., Ltd., product name: aluminum hydroxide) is used as a standard sample. Specifically, 23 μg, 122 μg, and 270 μg of aluminum hydroxide standard samples are accurately weighed using a microbalance, and the temperature is increased under the same conditions as above, and the area value of water molecules detached from aluminum hydroxide is measured, so that a calibration curve can be prepared. The moisture content of aluminum hydroxide herein is a value calculated from the mass reduction from 200° C. to 320° C. using a high-sensitivity differential thermobalance.

[0029] The spherical silica particles (X) of the present invention are heated from 50°C to 1000°C at a heating rate of 25°C / min, and the number of water molecules separated is 0.001-0.010mmoL / g, preferably 0.001-0.008mmoL / g, more preferably 0.002-0.008mmoL / g, and further preferably 0.003-0.007mmoL / g. In one embodiment, the number of water molecules separated may be 0.001-0.004mmoL / g, or 0.001-0.003mmoL / g. As mentioned above, polar functional groups such as silanol groups and adsorbed water are present on the surface of the silica particles, which become the main factors for worsening the dielectric loss tangent. The inventors of the present application have found that by setting the number of water molecules that are separated when heated from 50°C to 1000°C at a heating rate of 25°C / min (hereinafter sometimes also recorded as "separated water molecular weight") to less than 0.010 mmoL / g, a lower dielectric loss tangent can be achieved when filled into the resin. More surprisingly, it was also found that when the molecular weight of the separated water of the spherical silica particles is less than 0.001 mmoL / g, the value of the dielectric loss tangent deteriorates, similar to the case where the molecular weight of the separated water exceeds 0.010 mmoL / g. That is, by setting the molecular weight of the separated water of the spherical silica particles (X) involved in the present invention to a range of 0.001 to 0.010 mmoL / g, a lower dielectric loss tangent than conventional spherical silica particles can be achieved. The reason why the dielectric loss tangent deteriorates when the molecular weight of the desorbed water is less than 0.001 mmol / g is considered to be as follows: the spherical silica particles become less dispersed in the resin, resulting in deterioration of the dielectric loss tangent; and the amount of defects in the silica structure increases.

[0030] The specific surface area of ​​the spherical silica particles (X) of the present invention is 0.1 to 2.0 m 2 / g, preferably 0.3 to 2.0 m 2 / g, more preferably 0.5 to 2.0 m 2 / g, more preferably 0.7 to 1.8 m 2 In one embodiment, the specific surface area may also be 0.1 to 0.7 m 2 / g, or 0.1~0.5m 2 / g. The spherical silica particles (X) of the present invention have few foreign matters on the particle surface, so the specific surface area is small. By having a small specific surface area, it is easy to reduce the absolute number of polar functional groups such as adsorbed water and silanol groups on the surface of the silica particles. As a result, the spherical silica particles (X) of the present invention can simultaneously achieve low dielectric constant and low dielectric loss tangent when filled into a resin. It should be noted that the specific surface area of ​​the spherical silica particles can be measured by the BET method.

[0031] <Measurement method of specific surface area>

[0032] 1 g of spherical silica particles are filled into a measuring cell, and the specific surface area of ​​the spherical silica particles is measured using a fully automatic specific surface area diameter measuring device (e.g., manufactured by Mountech, product name: Macsorb HM model-1201 (BET single point method)). In addition, the degassing conditions before the measurement can be set to 200° C. and 10 minutes.

[0033] In order to make the number of water molecules detached from the spherical silica particles (X) within the above range, it is preferred to reduce the foreign matter on the surface of the spherical silica particles (X) and reduce the concavo-convexity (roughness) of the particle surface. In this way, the total amount of adsorbed water and polar functional groups on the surface of the spherical silica particles (X) can be reduced, and the amount of detached water molecules can be easily controlled within the range of 0.001 to 0.010 mmoL / g. In addition, by reducing the surface roughness of the particles, it is easy to control the specific surface area of ​​the spherical silica particles (X) within the range of 0.1 to 2.0 m 2 / g range.

[0034] Figure 1 This is an electron microscope photograph showing one embodiment of the spherical silica particles (X) according to the present invention. Figure 1 As shown in FIG. 1 , the spherical silica particles (X) according to the present invention have less foreign matter on the particle surface and less surface roughness. By having such a surface structure, the specific surface area can be 0.1 to 2.0 m 2 / g range, and the number of water molecules released when heated from 50°C to 1000°C at a certain heating rate is 0.001 to 0.010 mmoL / g. In addition, as a method for reducing foreign matter on the surface of the spherical silica particles (X), for example, a method of classifying the raw silica particles under wet conditions can be cited. The method for producing the spherical silica particles (X) according to the present invention will be described later.

[0035] The average circularity of the spherical silica particles (X) of the present invention is preferably 0.85 or more, more preferably 0.90 or more, and further preferably 0.94 or more. The average circularity of the spherical silica particles (X) is 0.85 or more, so that when the spherical silica particles (X) are mixed with a resin, the dispersibility in the resin is easily improved, and the dielectric properties are easily stabilized. In addition, it is easy to prevent the viscosity of the resin from increasing and the fluidity from decreasing, and the processability and filling properties are not easily deteriorated. Moreover, it is easy to adjust the specific surface area to 0.1 to 2.0 m 2In the present specification, the term “stable dielectric properties” means that when the dielectric constant and dielectric loss tangent of the resin composition containing the spherical silica particles (X) are measured, the variation of the values ​​due to different measurement positions is small.

[0036] The "average circularity" of the spherical silica particles (X) can be calculated by the following method.

[0037] <Average circularity>

[0038] After the spherical silica particles are fixed with carbon tape, osmium coating is performed. Then, a scanning electron microscope (e.g., manufactured by JEOL Ltd., product name: JSM-7001F SHL) is used to photograph the particles at a magnification of 500 to 50,000 times, and an image analyzer (manufactured by ROPER Co., Ltd., product name: Image-Pro Premier Ver.9.3) is used to calculate the projected area (S) and projected perimeter (L) of one particle, and the circularity is calculated by the following formula (1). The circularity is calculated for any 200 particles, and the average value is taken as the average circularity.

[0039] Circularity = 4πS / L 2 …(1)

[0040] The average particle size of the spherical silica particles (X) of the present invention is preferably 1 to 30 μm, more preferably 1 to 15 μm, and further preferably 1 to 6 μm. If the average particle size of the spherical silica particles (X) is within the above range, the filling property in the resin is easy to become better, and the dielectric constant and dielectric loss tangent of the resin composition are easy to adjust. In addition, the average particle size of the spherical silica particles (X) refers to the particle size (D50) when the cumulative value is equivalent to 50% in the cumulative particle size distribution based on the volume measured using a laser diffraction particle size distribution measuring device. The cumulative particle size distribution is represented by a distribution curve with the horizontal axis set to the particle size (μm) and the vertical axis set to the cumulative value (%).

[0041] The surface fractal dimension of the spherical silica particles (X) involved in the present invention is preferably 1.0 to 2.3, more preferably 1.0 to 2.1, and further preferably 1.0 to 1.9. The so-called "surface fractal dimension" here is an index representing the concavo-convex shape of the particle surface. The lower the value of the surface fractal dimension (Ds), the less concavo-convex on the particle surface and the smoother the surface. The spherical silica particles (X) involved in the present invention have a surface fractal dimension of 1.0 to 2.3, so that the dielectric loss tangent tends to become better when mixed with a resin. In addition, the surface fractal dimension of the spherical silica particles (X) can be measured by the following method.

[0042] <Method for measuring surface fractal dimension>

[0043] The spherical silica particles are directly placed in the transmission measurement sample cell of the X-ray diffraction analysis device (e.g., manufactured by Rigaku Corporation, product name: SmartLab) as it is, and the particles are measured under the following conditions using ultra-small angle X-ray scattering (USAXS). In addition, background removal and deblurring are performed during analysis. Deblurring is performed using analysis software (e.g., manufactured by Rigaku Corporation, product name: particle size-pore diameter analysis software NANO-Solver).

[0044] X-ray tube: Cu Kα,

[0045] Tube voltage-tube current: 45kV-200mA,

[0046] Detector: Scintillation counter,

[0047] Scanning range: 0.00~0.50deg,

[0048] Scan step: 0.0006deg,

[0049] Scanning speed: 0.03deg / min,

[0050] Incident side light splitting crystal: Ge(220)×2,

[0051] Light receiving side spectroscopic crystal: Ge(220)×2.

[0052] <Calculation method of surface fractal dimension>

[0053] The surface fractal dimension was calculated by the following method: First, the scattering angle 2θ was converted into a scattering vector q using the following formula (2). The X-ray wavelength λ was measured to be 0.154 nm.

[0054] q=4πsinθ / λ…(2)

[0055] Then, a double logarithmic graph showing the relationship between the scattering vector q and the intensity I(q) was prepared for the USAXS pattern after background removal and deblurring, and the graph was analyzed at q = 0.0124 to 0.0627 nm. -1 (2θ = 0.174 to 0.0882°) and the exponent part α in the approximation formula is substituted into the following formula (3) to calculate the surface fractal dimension (Ds).

[0056] Ds=6+α…(2)

[0057] The spherical silica particles (X) of the present invention can also be surface treated with a surface treatment agent. By surface treating with a surface treatment agent, the filling property of the spherical silica particles (X) of the present invention in the resin is easily improved. In addition, it is easy to reduce the polar functional groups on the particle surface, and it is easy to obtain spherical silica particles that can achieve a lower dielectric loss tangent. As a surface treatment agent, for example, silane coupling agents, aluminate coupling agents, etc. can be listed. These can be used alone, or two or more can be used in combination. Among these, from the viewpoint of easily reducing the polar functional groups on the particle surface, it is preferably treated with a silane coupling agent, and more preferably silane coupling agents with vinyl groups such as silazanes such as hexamethyldisilazane (HMDS), vinyltrimethoxysilane, etc. In addition, whether the spherical silica particles (X) have surface treatment, for example, IR, TG-DTA, mass spectrometry, etc. can be used to analyze the spherical silica particles (X) to confirm.

[0058] In the crystal structure of the spherical silica particles (X) of the present invention, the amorphous phase accounts for more than 95% by mass of the whole. By making the amorphous phase more than 95%, the thermal expansion coefficient is suppressed more effectively when filled in the resin. In addition, as long as the amorphous phase is within the above range, other crystalline phases such as quartz and cristobalite may also be contained.

[0059] The average particle density of the spherical silica particles (X) according to the present invention is preferably 1.8 to 2.4 g / cm 3 , more preferably 1.9 to 2.4 g / cm 3 , more preferably 2.0 to 2.4 g / cm 3 If the average particle density is 1.8 g / cm 3 If the average particle density is 2.4 g / cm 3 The following is the case where α-quartz, white silica, etc. are not easily contained in the crystal structure of the silica particles. Therefore, it is not easy to produce adverse effects on the physical properties of the silica particles, such as an increase in the thermal expansion coefficient. In addition, the average particle density of the spherical silica particles (X) can be measured by the following method.

[0060] <Method for measuring average particle density>

[0061] 2.0 g of spherical silica particles are placed in a measurement sample cell, and the average particle density is measured by a gas (helium) replacement method using a dry density meter (eg, manufactured by Shimadzu Corporation, product name: AccuPyc II 1340).

[0062] The spherical silica particles (X) of the present invention can achieve a lower dielectric loss tangent when filled into a resin. In one embodiment, the dielectric constant of the resin sheet containing the spherical silica particles (X) of the present invention prepared by the method described below at 35 GHz is preferably 3.0 or less. In addition, the dielectric loss tangent of the resin sheet at 35 GHz is preferably less than 4.8×10 -4 , more preferably 4.5×10 -4 Below, more preferably 4.0×10 -4 the following.

[0063] [Method for producing spherical silica particles (X)]

[0064] Next, one embodiment of the method for producing the spherical silica particles (X) according to the present invention will be described. In addition, the method for producing the spherical silica particles (X) according to the present invention is not limited to the following production method.

[0065] The method for producing spherical silica particles (X) in the present embodiment includes: classifying amorphous spherical silica particles (hereinafter sometimes referred to as "spherical silica particles (A)") (step (i)), and then heat treating at a temperature of 800 to 1200°C (step (ii)). In addition, the method for producing spherical silica particles (X) in the present embodiment may also include: preparing amorphous spherical silica particles (step (i')).

[0066] <Preparation process: process (i')>

[0067] The method for producing spherical silica particles (X) in the present embodiment may include a step (i′) of preparing amorphous spherical silica particles (spherical silica particles (A)).

[0068] Spherical silica particles (A) can use spherical silica particles prepared by a conventionally known method. From the viewpoint of productivity, spherical silica particles prepared by a powder melting method are preferred. In the present embodiment, step (i') may also be a step of preparing spherical silica particles (A) by a powder melting method. In addition, the term "amorphous spherical silica particles" as used in the present invention refers to spherical silica particles having a silica purity of 98% or more and an amorphous phase of 95% or more by mass of the whole.

[0069] The powder melting method is a method of melting and spheroidizing crushed materials such as silica sand and silica (hereinafter sometimes also recorded as "crude raw materials") under high temperature conditions above the melting point of the crude raw materials using flames, plasma, electric furnaces, gas furnaces, etc. The melting atmosphere is not particularly limited, and from the viewpoint of economy, it is preferably carried out under an atmospheric atmosphere. The average particle size (D50) of the crude raw material is preferably 0.1 to 100 μm, more preferably 0.2 to 50 μm, and further preferably 0.3 to 10 μm. In one embodiment, the average particle size of the crude raw material may be 10 to 100 μm, or 50 to 100 μm.

[0070] The average particle size (D50) of the spherical silica particles (A) (hereinafter referred to as "average particle size (Da50)") is preferably 1 to 30 μm, and more preferably 1 to 15 μm. In one embodiment, the average particle size (Da50) may be 1 to 10 μm, or 2 to 8 μm. In addition, from the viewpoint of easily adjusting the average circularity of the finally obtained spherical silica particles (X) to 0.85 or more, the average circularity is preferably 0.85 or more, and more preferably 0.90 or more. In addition, the specific surface area (hereinafter referred to as "specific surface area (Sa)") of the spherical silica particles (A) is not particularly specified, and may be, for example, 0.1 to 10 m 2 The average particle size (Da50), average circularity and specific surface area (Sa) of the spherical silica particles (A) can be measured by the same measurement methods as those for the spherical silica particles (X).

[0071] After the step (i') is carried out as necessary to obtain the spherical silica particles (A), the spherical silica particles (A) are classified as follows.

[0072] <Classification process: process (i)>

[0073] The method for producing spherical silica particles (X) in the present embodiment includes: step (i) of classifying spherical silica particles (A). Step (i) is a step of placing the spherical silica particles (A) into a classifying device and centrifuging them at a certain circumferential speed to remove fine particles from the spherical silica particles (A). As a classifying device, for example, a gravity field classifier, a centrifugal field classifier, etc. can be used.

[0074] Step (i) is preferably a step of removing particles of 0.9 μm or less contained in the spherical silica particles (A). In addition, step (i) is preferably a step of removing fine foreign matter attached to the surface of the spherical silica particles (A). The so-called "foreign matter on the surface of the spherical silica particles (A)" refers to, for example, Figure 2The particles attached to the surface of the spherical silica particles (A) are shown. The spherical silica particles (A) are classified to remove fine foreign matter on the surface of the particles, so that spherical silica particles with less surface unevenness and a small specific surface area can be easily obtained. Moreover, it is easy to adjust the number of water molecules released from the finally obtained spherical silica particles (X) in the temperature range of 50°C to 1000°C to the range of 0.001 to 0.010 mmoL / g. The spherical silica particles obtained after step (i) (after classification treatment) are described as "spherical silica particles (B)" below.

[0075] Step (i) may be a step of removing foreign matter from the surface of the spherical silica particles (A) to reduce the specific surface area of ​​the spherical silica particles (A). In one aspect, the specific surface area (Sb) of the spherical silica particles (B) obtained after step (i) relative to the specific surface area (Sa) of the spherical silica particles (A), that is, (Sb) / (Sa), may be 0.2 or more and 0.6 or less, or 0.3 or more and 0.6 or less.

[0076] In the production method of the present embodiment, step (i) may be a step of classifying the spherical silica particles (A) to obtain spherical silica particles (B) having a surface fractal dimension of 1.0 to 2.3.

[0077] Step (i) may be a step of removing fine particles from the spherical silica particles (A) by dry classification or a step of removing fine particles from the spherical silica particles (A) by wet classification. Wet classification is preferred from the viewpoint of efficiently removing particles of 0.9 μm or less.

[0078] (Wet Classification)

[0079] When step (i) is wet classification, the slurry containing the spherical silica particles (A) and the dispersion medium is placed in a classifier. When step (i) is wet classification, the classifier may be, for example, a gravity field classifier, a centrifugal field classifier, or the like.

[0080] Examples of the dispersion medium include water (including pure water, ion-exchanged water, etc.), and organic solvents such as ethanol and acetone. Among them, from the viewpoint of the ease of dispersion of the spherical silica particles (A) and economic efficiency, it is preferred to contain at least water as the dispersion medium.

[0081] The proportion of water in the dispersion medium is more preferably 50 to 100% by mass relative to the total mass of the dispersion medium. In addition, the concentration of the spherical silica particles (A) in the slurry is preferably 1 to 50% by mass, more preferably 20 to 40% by mass relative to the total mass of the slurry.

[0082] As a method for preparing the slurry, for example, there is mentioned a method in which the spherical silica particles (A) are added to a dispersion medium so as to have a desired solid content concentration, and then stirred at room temperature for 1 to 24 hours.

[0083] When using a classifier described in Examples below, the rotor peripheral speed during wet classification is preferably 10 to 30 m / s, more preferably 20 to 30 m / s, from the viewpoint of efficiently classifying fine particles.

[0084] The temperature during wet classification is not particularly limited, but is preferably room temperature from the viewpoint of economic efficiency.

[0085] When step (i) is wet classification, the classified slurry is allowed to stand and the supernatant is removed to obtain spherical silica particles (B). Then, the spherical silica particles (X) are further heat-treated as follows. In addition, the spherical silica particles (B) may be dried at 40 to 200° C. for 1 to 24 hours before step (ii). Alternatively, the drying may be performed under vacuum.

[0086] <Heat treatment step: step (ii)>

[0087] The method for producing spherical silica particles (X) in the present embodiment includes the following steps: after step (i), further heat treatment is performed at a temperature of 800 to 1200°C. In step (ii), the heating temperature of the spherical silica particles (B) is 800 to 1200°C, preferably 900 to 1100°C. By heat treatment at a high temperature of 800 to 1200°C, it is easy to obtain spherical silica particles (X) in which the number of detached water molecules is within the range. Such spherical silica particles (X) can achieve a lower dielectric loss tangent when filled into a resin. As a heating device, for example, an electric furnace, a gas stove, etc. can be used. In addition, from the viewpoint of reducing the amount of water, step (ii) is preferably performed under a nitrogen or argon atmosphere, or under a vacuum atmosphere. In addition, the heating time is preferably 1 to 24 hours, more preferably 2 to 8 hours. If the heating time is 1 to 24 hours, productivity is also likely to become good. In one embodiment, step (ii) may be performed by heating the spherical silica particles (B) at 800 to 1200° C. for 1 to 24 hours, or may be performed by heating the spherical silica particles (B) at 800 to 1200° C. for 2 to 8 hours.

[0088] Spherical silica particles (X) can be obtained by a method including the above steps (i) to (ii) (according to needs, by a method including steps (i'), steps (i) and steps (ii)). In addition, after step (ii), the spherical silica particles (X) can also be surface-treated with a surface treatment agent as needed. In addition, the spherical silica particles (X) obtained after step (i) or step (ii), or after an optional surface treatment step, sometimes become aggregates. Therefore, after these steps, a pulverization treatment can be performed as needed. As a pulverization method, it is preferably carried out under dry conditions without contact with moisture, for example, an agate mortar, a ball mill, a vibration mill, a jet mill, etc. can be used.

[0089] The spherical silica particles (X) obtained by the production method of this embodiment have, for example, Figure 1 On the other hand, Figure 2 This is an electron microscope photograph showing one form of amorphous spherical silica particles (spherical silica particles (A)) before classification. Figure 1 , 2 As can be seen from the comparison, a large amount of very fine foreign matter is attached to the surface of the spherical silica particles (A), and the specific surface area (Sa) becomes larger due to the fine foreign matter. According to the manufacturing method involved in this embodiment, the fine foreign matter on the surface of the spherical silica particles (A) is easily removed by step (i), and as a result, it is easy to obtain Figure 1 The spherical silica particles (X) shown have less surface foreign matter and a reduced specific surface area. When the spherical silica particles (X) with less surface foreign matter and a small specific surface area are filled into the resin, it is easy to achieve a lower dielectric loss tangent. That is, the manufacturing method in this embodiment is more preferably a method that satisfies the following conditions (1) and (2).

[0090] Condition (1): The average particle size (Dx50) of the spherical silica particles (X) relative to the average particle size (Da50) of the spherical silica particles (A), that is, (Dx50) / (Da50) is 0.8 or more and 1.2 or less.

[0091] Condition (2): The specific surface area (Sx) of the spherical silica particles (X) relative to the specific surface area (Sa) of the spherical silica particles (A), that is, (Sx) / (Sa) is 0.2 or more and 0.6 or less.

[0092] By satisfying the conditions (1) to (2), it is easy to obtain spherical silica particles (X) having a small specific surface area while maintaining the average particle size (Da50) of the spherical silica particles (A).

[0093] [use]

[0094] The spherical silica particles (X) according to the present invention can achieve a low dielectric constant and a low dielectric loss tangent when filled into a resin, and therefore can be suitably used as a filler for a resin material.

[0095] [Resin composition]

[0096] The resin composition according to the present invention contains the spherical silica particles (X) and at least one resin selected from a thermoplastic resin and a thermosetting resin.

[0097] The content of the spherical silica particles (X) in the resin composition is not particularly limited and can be appropriately adjusted according to the purpose. For example, when used for high-frequency band substrate materials and insulating materials, it can be blended in the range of 1 to 95% by mass relative to the total mass of the resin composition, more preferably in the range of 10 to 80% by mass.

[0098] <Resin>

[0099] The resin composition of the present invention contains at least one resin selected from thermoplastic resins and thermosetting resins. More specifically, for example, polyethylene resins; polypropylene resins; epoxy resins; silicone resins; phenolic resins; melamine resins; urea resins; unsaturated polyester resins; fluororesins; polyamide resins such as polyimide resins, polyamide-imide resins, and polyether-imide resins; polyester resins such as polybutylene terephthalate resins and polyethylene terephthalate resins; polyphenylene sulfide resins; fully aromatic polyester resins; polysulfone resins; liquid crystal polymer resins; polyethersulfone resins; polycarbonate resins; maleimide-modified resins; ABS resins; AAS (acrylonitrile-acrylic rubber-styrene) resins; AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins; hydrocarbon elastomer resins; polyphenylene ether resins; aromatic polyene resins, etc. These can be used alone or in combination of two or more.

[0100] When the resin composition of the present invention is used as a high-frequency band substrate material or an insulating material, a known low-dielectric resin used in this application can be used. Specifically, as the low-dielectric resin, at least one resin selected from a hydrocarbon elastomer resin, a polyphenylene ether resin, and an aromatic polyene resin can be used. Among them, a hydrocarbon elastomer resin or a polyphenylene ether resin is preferred.

[0101] The resin composition according to the present invention may contain a curing agent, a curing accelerator, a release agent, a coupling agent, a colorant, a flame retardant, an ion scavenger, and the like within a range not impairing the effects of the present invention.

[0102] <Method for producing resin composition>

[0103] The manufacture method of resin combination is not particularly limited, and can be manufactured by stirring, dissolving, mixing, and dispersing each material of a predetermined amount. The devices for mixing, stirring, and dispersing of these mixtures are not particularly limited, and a pounding machine, a three-roller grinder, a ball mill, a planetary mixer, etc. equipped with stirring and a heating device can be used. In addition, these devices can also be appropriately combined for use.

[0104] As described above, the resin composition containing the spherical silica particles (X) of the present invention can achieve a low dielectric constant and a lower dielectric loss tangent. In addition, the resin composition containing the spherical silica particles of the present invention has a low viscosity, so it has good fluidity and excellent moldability.

[0105] Example

[0106] The present invention will be described in detail below with reference to Examples, but the present invention is not limited to the following descriptions.

[0107] As spherical silica particles (A), spherical silica particles (A-1) shown in Table 1 (manufactured by Denka Co., Ltd., trade name: FB-5D, specific surface area 2.3 m 2 / g) and spherical silica particles (A-2) (manufactured by Denka Co., Ltd., trade name: FB-3SDC, specific surface area: 3.3 m 2 / g). In addition, the average circularity, average particle density, average particle size, specific surface area and desorbed water molecular weight of the spherical silica particles (A-1) and (A-2), and the dielectric constant and dielectric loss tangent when made into a resin sheet are values ​​measured according to the method described below.

[0108] [Table 1]

[0109]

[0110] [Example 1]

[0111] 2 kg of spherical silica particles (A-1) shown in Table 1 were added to 3 kg of pure water and stirred at room temperature for 6 hours to prepare a slurry with a particle concentration of 40% by mass. This slurry was put into a classifier (manufactured by Satake Chemical Machinery Industry Co., Ltd., product name: SATAKE i Classifier (registered trademark) standard machine) for wet classification. The classification conditions were set to rotor circumferential speed: 26 m / s, particle discharge rate: 10 L / hr. The slurry after removing the particles was decanted to remove the supernatant, and the obtained spherical silica particles (B) were dried at 110°C for 24 hours. The dried spherical silica particles (B) were crushed with a mortar and 50 g were taken and placed in an alumina crucible, and an electric furnace (manufactured by Fuji Electric Wave Industry Co., Ltd., product name: HiMulti (registered trademark) 10000) was used. Heat treatment was performed for 4 hours at a temperature of 1000°C in the electric furnace under a nitrogen atmosphere. Then, the spherical silica particles (X) were recovered after natural cooling until the furnace reached room temperature. The surface fractal dimension, specific surface area, molecular weight of desorbed water, average particle size, average circularity and average particle density of the obtained spherical silica particles (X) were measured by the following method. In addition, the surface state of the spherical silica particles (X) was observed by the following method to confirm whether there were particles on the surface. The results are shown in Table 2.

[0112] <Method for Determining the Number of Desorbed Water Molecules>

[0113] Using a gas chromatograph mass spectrometer (manufactured by JEOL Ltd., product name: JMS-Q1500GC) and a thermal decomposition device (manufactured by Frontier Lab, product name: PY-3030D), 15 μg of spherical silica particles were heated from 50°C to 1000°C at a heating rate of 25°C / min in a helium atmosphere. The area value of the mass spectrum (m / z=18) obtained in the range of 50°C to 1000°C was calculated, and the number of water molecules detached was calculated from the calibration curve. In addition, for the calibration curve, the area value of the number of water molecules detached (m / z=18) of an aluminum hydroxide sample (manufactured by Kojundo Chemical Research Institute Co., Ltd., product name: aluminum hydroxide) as a standard sample was used. Specifically, 23 μg, 122 μg, and 270 μg of aluminum hydroxide standard samples were accurately weighed using a microbalance, and the temperature was raised under the same conditions as above, and the area value of water molecules detached from aluminum hydroxide was measured to prepare a calibration curve. In addition, the moisture content of the aluminum hydroxide sample was calculated by the following method. A high-sensitivity differential differential thermobalance (manufactured by NETZSCH, product name: STA 2500Regulus) was used to measure the mass reduction of aluminum hydroxide particles (manufactured by Kojundo Chemical Research Institute Co., Ltd., product name: aluminum hydroxide, ALI06PB) at 200°C to 320°C (heating conditions: heating from room temperature (23°C) to 800°C at a heating rate of 10°C / min, carrier gas: air, measurement container: platinum pan, sample amount: 13 mg).

[0114] <Measurement method of specific surface area>

[0115] 1 g of spherical silica particles were filled into a measuring cell, and the specific surface area of ​​the spherical silica particles was measured using a fully automatic specific surface area diameter measuring device (Mountech, product name: Macsorb HM model-1201 (BET single point method)). The degassing conditions before the measurement were set at 200°C for 10 minutes.

[0116] <Method for measuring average circularity>

[0117] After the spherical silica particles are fixed to the sample stage with a carbon tape, osmium coating is performed. Then, an image with a magnification of 500 to 50,000 times and a resolution of 1280×1024 pixels taken with a scanning electron microscope (manufactured by JEOL Ltd., JSM-7001F SHL) is read into a computer. For this image, an image analyzer (manufactured by ROPER Co., Ltd., product name: Image-Pro Premier Ver.9.3) is used to calculate the projected area (S) and projected perimeter (L) of one particle, and the circularity is calculated by the following formula (1). The circularity is calculated for any 200 particles, and the average value is taken as the average circularity.

[0118] Circularity = 4πS / L 2 …(1)

[0119] <Method for measuring average particle size>

[0120] The average particle size was measured using a laser diffraction particle size distribution analyzer (manufactured by Beckman Coulter, trade name: LS13 320). First, a 50 cm 3 Pure water and 0.1 g of spherical silica particles are dispersed for 1 minute using an ultrasonic homogenizer (manufactured by BRANSON, trade name: SFX250). The dispersion of the spherical silica particles that have been dispersed is added dropwise to a laser diffraction particle size distribution measuring device using a dropper, and the measurement is performed 30 seconds after the addition of the predetermined amount. The particle size distribution is calculated from the data of the light intensity distribution of the diffracted / scattered light of the spherical silica particles detected by the sensor in the laser diffraction particle size distribution measuring device. The average particle size is calculated from the particle size when the cumulative value is equivalent to 50% in the volume-based cumulative particle size distribution of the measured particle size.

[0121] <Method for measuring average particle density>

[0122] 2.0 g of spherical silica particles were placed in a sample cell for measurement, and the average particle density was measured by a gas (helium) replacement method using a dry density meter (manufactured by Shimadzu Corporation, product name: AccuPyc II 1340).

[0123] <Method for measuring surface fractal dimension>

[0124] The spherical silica particles were directly placed in the transmission measurement sample cell of the X-ray diffraction analysis device (manufactured by Rigaku Co., Ltd., product name: SmartLab) as they are, and the particles were measured under the following conditions using the ultra-small angle X-ray scattering method (USAXS). During analysis, background removal and deblurring were performed. Deblurring was performed using analysis software (manufactured by Rigaku Co., Ltd., product name: particle size-pore diameter analysis software NANO-Solver).

[0125] X-ray tube: Cu Kα,

[0126] Tube voltage-tube current: 45kV-200mA,

[0127] Detector: Scintillation counter,

[0128] Scanning range: 0.00~0.50deg,

[0129] Scan step: 0.0006deg,

[0130] Scanning speed: 0.03deg / min,

[0131] Incident side light splitting crystal: Ge(220)×2,

[0132] Light receiving side spectroscopic crystal: Ge(220)×2.

[0133] <Calculation method of surface fractal dimension>

[0134] The surface fractal dimension was calculated by the following method. First, the scattering angle 2θ was converted into a scattering vector q using the following formula (2). The measurement X-ray wavelength λ was set to 0.154 nm.

[0135] q=4πsinθ / λ…(2)

[0136] Then, a double logarithmic graph showing the relationship between the scattering vector q and the intensity I(q) was prepared for the USAXS pattern after background removal and deblurring. -1 The exponential approximation is performed in (2θ=0.174-0.0882°). The exponential part α in the approximation is substituted into the following equation (3) to calculate the surface fractal dimension (Ds).

[0137] Ds=6+α···(3)

[0138] <Observation of particle surface>

[0139] The surface of the spherical silica particles (X) was observed with an electron microscope to evaluate the presence or absence of fine particles on the particle surface.

[0140] (Evaluation Criteria)

[0141] Acceptable: Fine particles have been removed from the surface of the spherical silica particles (X), and the surface irregularities have become smaller.

[0142] Unacceptable: A large number of fine particles adhere to the surface of the spherical silica particles (X).

[0143] <Evaluation of Dielectric Properties (Dielectric Constant and Dielectric Loss Tangent)>

[0144] Spherical silica particles (X) and polyethylene resin powder (manufactured by Sumitomo Seika Co., Ltd., trade name: FLO-THENE (registered trademark) UF-20S) were weighed so that the filling amount of spherical silica particles (X) was 40% by volume, and a vibrating mixer (manufactured by Resodyn Co., Ltd.) was used to mix at an acceleration of 60G and a processing time of 2 minutes to obtain a resin composition. The obtained resin composition was put into a metal frame with a diameter of 3 cm in an amount of about 0.3 mm in thickness, and was sheeted under the conditions of 140°C, 5 minutes, and 30000N using a nanoimprint device (manufactured by SCIVAX Co., Ltd., trade name: X-300). The obtained sheet was cut into a size of 1.5 cm × 1.5 cm to obtain an evaluation sample.

[0145] Then, a 36GHz cavity resonator (manufactured by SAMTECH) was connected to a vector network analyzer (85107, manufactured by Keysight Technologies), and the evaluation sample was configured to block a hole with a diameter of 10mm set in the cavity resonator, and the resonant frequency (f0) and the unloaded Q value (Qu) were measured. The evaluation sample was rotated 60 degrees for each measurement, and the same measurement was repeated 5 times. The average value of the obtained f0 and Qu values ​​was used as the measured value, and the dielectric constant was calculated from f0 using the analytical software (software manufactured by SAMTECH Co., Ltd.), and the dielectric loss tangent (tanδc) was calculated from Qu. In addition, the measurement was carried out under the conditions of a measuring temperature of 20°C and a humidity of 60%RH. The values ​​of the obtained dielectric constant and dielectric loss tangent were evaluated according to the following evaluation criteria. The results are shown in Table 2.

[0146] (Evaluation Criteria)

[0147] <Dielectric constant>

[0148] 3 points: Dielectric constant is below 3.0

[0149] 2 points: Dielectric constant is more than 3.0 and less than 3.2

[0150] 1 point: Dielectric constant is more than 3.2 and less than 3.4

[0151] 0 points: Dielectric constant exceeds 3.4

[0152] <Dielectric loss tangent>

[0153] 3 points: Dielectric loss tangent is less than 4.0×10 -4

[0154] 2 points: Dielectric loss tangent is 4.0×10 -4 More than and less than 4.5×10 -4

[0155] 1 point: Dielectric loss tangent is 4.5×10-4 More than and less than 5.0×10 -4

[0156] 0 point: Dielectric loss tangent is 5.0×10 -4 above

[0157] <Overall Evaluation>

[0158] The dielectric constant and dielectric loss tangent points are summed up and the dielectric properties are evaluated according to the following standards.

[0159] Excellent: The number of points for both the dielectric constant and the dielectric loss tangent is 3 (total number of points is 6).

[0160] Good: One of the dielectric constant or dielectric loss tangent is 3 points, and the other is 2 points (total 5 points).

[0161] Yes: The number of points for both the dielectric constant and the dielectric loss tangent is 2 (the total number of points is 4).

[0162] Not allowed: The number of points for either the dielectric constant or the dielectric loss tangent is less than 2 (the total number of points is 4 or less).

[0163] [Examples 2 to 3 and Comparative Examples 1 to 4]

[0164] Spherical silica particles (X) were obtained under the manufacturing conditions shown in Table 2. In addition, Comparative Examples 1 to 2 and 4 are examples of manufacturing spherical silica particles (X) without performing step (i) (classification step). For the spherical silica particles (X) of each example, the specific surface area, the molecular weight of desorbed water, the average particle size, the average circularity, the surface fractal dimension, and the average particle density were measured in the same manner as in Example 1. In addition, the surface state and dielectric properties of the particles were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0165] [Example 4]

[0166] Spherical silica particles (X) were obtained under the manufacturing conditions shown in Table 2. 1 mass part of hexamethyldisilazane (recorded as "HMDS" in Table 2) (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: SZ-31) was added as a surface treatment agent to 100 mass parts of the obtained spherical silica particles (X). Then, after mixing for 2 minutes at an acceleration of 60G using a vibration mixer (manufactured by Resodyn, product name: LabRAMII), the mixed powder was dried for 24 hours at 120°C and below -133Pa using a mixed powder vacuum dryer to obtain surface-treated spherical silica particles (X). For the obtained spherical silica particles (X), the specific surface area, the molecular weight of desorption of water, the average particle size, the average circularity, the surface fractal dimension, and the average particle density were determined in the same manner as in Example 1. In addition, the surface state and dielectric properties of the particles were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0167] [Example 5]

[0168] Spherical silica particles (X) were obtained under the manufacturing conditions shown in Table 2. 1 mass part of vinyl triethoxysilane (recorded as "vinyl" in Table 2) (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBE-1003) was added as a surface treatment agent to 100 mass parts of the obtained spherical silica particles (X). Then, after mixing for 2 minutes at an acceleration of 60G using a vibration mixer (manufactured by Resodyn, product name: LabRAMII), the mixed powder was dried for 24 hours at 120°C and below -133Pa using a mixed powder vacuum dryer to obtain surface-treated spherical silica particles (X). For the obtained spherical silica particles (X), the specific surface area, the molecular weight of desorption of water, the average particle size, the average circularity, the surface fractal dimension, and the average particle density were determined in the same manner as in Example 1. In addition, the surface state and dielectric properties of the particles were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0169] [Table 2]

[0170]

[0171] As shown in Table 1, the spherical silica particles (X) of Examples 1 to 5 satisfying the constitution of the present invention have a lower dielectric loss tangent than the spherical silica particles of the comparative example. In addition, the spherical silica particles (X) of Examples 1 to 5 were observed under an electron microscope, and the microparticles were removed from the surface of the particles. On the other hand, the specific surface area exceeded 2.0 m 2 / g and the amount of desorbed water molecules exceeds 0.010mmoL / g, the dielectric loss tangent of the resin sheet is high. It is believed that the reason is that the specific surface area of ​​the particles is large and there are many adsorbed water and functional groups on the surface of the particles. In addition, for the spherical silica particles in Comparative Example 3, in which the number of desorbed water molecules is less than 0.001mmoL / g, the dielectric loss tangent of the resin sheet is also high. It is believed that the reason is that the dispersion of the particles in the resin sheet is worse than that in the examples, and the defects in the particles increase due to the high processing temperature. In addition, for the spherical silica particles in Comparative Example 3, in which the number of desorbed water molecules is 0.008mmoL / g and the specific surface area exceeds 2.0m 2 / g of the spherical silica particles of Comparative Example 4, the value of the dielectric loss tangent of its resin sheet is also high. It is believed that the reason is that for particles with a large specific surface area, the processing temperature must be increased in order to reduce the amount of adsorbed water and functional groups. As a result, the dispersion of particles in the resin sheet is worse than that of the embodiment, and the defects in the particles increase due to the high processing temperature, etc., as in Comparative Example 3. From the above results, it is confirmed that the spherical silica particles (X) of the present invention can achieve a lower dielectric loss tangent when filled in the resin.

[0172] [Industrial Applicability]

[0173] The spherical silica particles of the present invention can achieve a lower dielectric loss tangent when filled into a resin. Such spherical silica particles can be suitably used as a filler for resin materials such as high-frequency band substrate materials and insulating materials.

Claims

1. A spherical silica particle, characterized in that: When the spherical silica particles are heated from 50°C to 1000°C at a heating rate of 25°C / min, the number of water molecules released from the spherical silica particles is 0.001 to 0.010 mmoL / g, and the specific surface area is 0.1 to 2.0 m 2 / g.

2. The spherical silica particles according to claim 1, wherein The spherical silica particles have an average circularity of 0.85 or more.

3. The spherical silica particles according to claim 1 or 2, wherein The surface fractal dimension of the spherical silica particles is 1.0 to 2.

3.

4. The spherical silica particles according to claim 1 or 2, wherein The average particle size of the spherical silica particles is 1 to 30 μm.

5. The spherical silica particles according to claim 1 or 2, wherein The spherical silica particles are surface treated with a surface treatment agent. The spherical silica particles according to claim 1 or 2, which are used for resin filling. 7 . A resin composition comprising the spherical silica particles according to claim 1 , and at least one resin selected from a thermoplastic resin and a thermosetting resin.

Citation Information

Patent Citations

  • Filler for electronic material, method for producing the same, method for producing resin composition for electronic material, substrate for high frequency, and slurry for electronic material

    JP2020097498A

  • Method for producing metal oxide particle material

    JP2020138880A

  • Spherical crystalline silica particles and method for producing same

    WO2016031823A1

  • Spherical silica powder

    CN113614036A

  • Spherical silica powder

    CN115515899A